Modelling Impact of Moratorium on Electronic Transmissions using CGE: A Critique - BANGA, RASHMI (Advances in Social Sciences Research Journal, 2019)
The paper presents a detailed critique of estimating economic impact of moratorium on custom duties on electronic transmissions using CGE modelling, which has been undertaken by the European Centre for International Political Economy (ECIPE). Electronic transmissions are ‘on-line’ deliveries of digitizable products like music CDs, films, e-books, software and printed material. Since 1998, moratorium on custom duties on electronic transmissions has been renewed every two years in the WTO. ECIPE paper estimates the economic impact of removal of the moratorium. Using GTAP model, the analysis applies arbitrary tariffs on four broad services sectors and presents the results as economic impact of removal of moratorium. This is misleading for the policymakers. The model does not have product-level data or dis-aggregated services data in order to identify electronic transmissions. Applying tariffs on broad services sectors also challenges the commitments taken by the developing countries in the GATS.